2011
DOI: 10.1186/1471-2474-12-285
|View full text |Cite
|
Sign up to set email alerts
|

A strong association between non-musculoskeletal symptoms and musculoskeletal pain symptoms: results from a population study

Abstract: BackgroundThere is a lack of knowledge about the pattern of symptom reporting in the general population as most research focuses on specific diseases or symptoms. The number of musculoskeletal pain sites is a strong predictor for disability pensioning and, hence, is considered to be an important dimension in symptom reporting. The simple method of counting symptoms might also be applicable to non-musculoskeletal symptoms, rendering further dimensions in describing individual and public health. In a general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 41 publications
5
38
1
2
Order By: Relevance
“…Previous studies have also found that high symptom reporting was associated with an increased number of reported bodily pain sites,21 as well as greater use of healthcare and increased mortality, even after controlling for relevant confounders 22. Interestingly, a recent study in general practice patients also found that as symptom reports increased, so did the patients’ belief that they were suffering from an unexplained condition such as amalgam poisoning, electromagnetic sensitivity or chronic fatigue syndrome 23…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have also found that high symptom reporting was associated with an increased number of reported bodily pain sites,21 as well as greater use of healthcare and increased mortality, even after controlling for relevant confounders 22. Interestingly, a recent study in general practice patients also found that as symptom reports increased, so did the patients’ belief that they were suffering from an unexplained condition such as amalgam poisoning, electromagnetic sensitivity or chronic fatigue syndrome 23…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, some individuals might have a tendency to report any symptoms, whereas others not report similar symptoms [39]. However, we have collected no information on the personality traits which could influence reporting patterns of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, with the exception of small, isolated societies, 2,3 studies of co-occurrence of cLBP and other symptoms have been conducted in affluent countries of the West, notably Norway. 4-8 The population of China is 1.4 billion, which is larger than the combined populations of affluent (“high income”) countries of the West. 9 …”
Section: Introductionmentioning
confidence: 99%